Fabrication and characterization of MID IR quantum cascade laser devices - Hou, Kunqi (2019)
The QCLs have an important role in MID-ID lasers, and it has many applications which make life better. This dissertation has an introduction of its application mainly focus on telecommunication, gas-sensing, medical use, and military use. After that, it briefly introduces several of the MID-IR light sources and compares the advantages and disadvantages of each method. And illustrate the significant advantages of QCLs in this wavelength. Chapter two mainly describes the basic theory of QCLs. It introduces the quantized electronic states in a single quantum well as well as the tunneling transition mechanism between different quantum wells. And then it introduces the active region in QCLs, including how to achieve the population inversion and how to achieve the high optical gain by cascading process. Since this dissertation mainly talks about MID-IR QCLs, so it also introduces how the waveguide form for MID-IR QCLs. Chapter three mainly talks about the fabrication steps of MID-IR QCLs. The fabrication process of this device is more complicated than another laser device. From the initial stage (active region grew by NTU on an InP substrate), by going through many process steps such as photolithography, oxidation, plasma etching, vacuum evaporation deposition, etc. The ridge structure can be formed. Chapter four mainly talks about the characterization of the fabricated device by using many types of equipment, waveform generator, oscilloscope, FTIR system, etc. The characterization includes average and peak output power relevant to the input current and input voltage. And it also contains the output power for different wavelength. For the device in this dissertation, the peak output wavelength is 10nanometer, and it has a good L-I-V curve.